LA SÁTIRA PRESENTE EN LA OBRA “PINCELADAS DE FUEGO” DEL POETA FALCONIANO ÁNGEL JOSÉ CURIEL. UN DESCENDIENTE DE LA COMUNIDAD JUDÍA SEFARDÍES (De la Crítica, 2023)
The present study was carried out based on the analysis of the imbued satirical elements in the poems of the Falconian poet Angel Jose Curiel, in his majestic work "Pinceladas de Fuego." The purpose of the research seeks to investigate the position that the author has against the evils that afflict the Coriana society, both in the development of the behavior of citizens in common life and their actions in the civil service of the public administrations of the institutions, evidencing the complaints through his artistic pen as a sharp dart against the immoral scourges of corruption and bureaucracy. Consequently, through this working paper brings to the fore the discussion and reflection that society and its institutions still persist vestiges of social and immoral decomposition that questions and claims a transformation, that it is always necessary to take into account the critical denunciation that feeds the conscience, that allows each day to obtain a new citizen, with values that allow the good metabolism of society.